2010
DOI: 10.1007/s10827-010-0250-7
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for frequency-dependent extracellular impedance from the transfer function between extracellular and intracellular potentials

Abstract: We examine the properties of the transfer function F T = V m /V LFP between the intracellular membrane potential (V m ) and the local field potential (V LFP ) in cerebral cortex. We first show theoretically that, in the subthreshold regime, the frequency dependence of the extracellular medium and that of the membrane potential have a clear incidence on F T . The calculation of F T from experiments and the matching with theoretical expressions is possible for desynchronized states where individual current sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 33 publications
8
55
0
Order By: Relevance
“…This work provides the first direct experimental proof of effects related to these microscale inhomogeneities, as we show that electrically as well as physically, extracellular space in the brain indeed is not homogenous. Our results are in general agreement with those of Bédard et al (2004) in that we find that inhomogeneity of the extracellular space leads to additional filtering and amplitude attenuation of the extracellular signal, though here we do not address the issue of the frequency dependence of extracellular signal propagation.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This work provides the first direct experimental proof of effects related to these microscale inhomogeneities, as we show that electrically as well as physically, extracellular space in the brain indeed is not homogenous. Our results are in general agreement with those of Bédard et al (2004) in that we find that inhomogeneity of the extracellular space leads to additional filtering and amplitude attenuation of the extracellular signal, though here we do not address the issue of the frequency dependence of extracellular signal propagation.…”
Section: Discussionsupporting
confidence: 91%
“…Typically this has been modeled as electrically homogenous (Gold et al, 2006;Nunez and Srinivasan, 2006;Lindén et al, 2011), although the effect of the inhomogeneity of the extracellular space has been considered by some (Bédard et al, 2004;Bazhenov et al, 2011). This work provides the first direct experimental proof of effects related to these microscale inhomogeneities, as we show that electrically as well as physically, extracellular space in the brain indeed is not homogenous.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taking into account ionic diffusion requires to revise the "forward" approach, because the attenuation law does not follow a 1/r 2 law but rather a Yukawa-type law, while the extracellular medium is associated to a Warburg-type impedance. In a previous study, we showed that indeed a Warburg-type impedance could account for the transfer function between intracellular and extracellular potentials [19] (for frequencies comprised between 3 and 300 Hz). It is also consistent with measurements of conductivity and permittivity [12] (but see Ref.…”
Section: Discussionmentioning
confidence: 89%
“…Despite this, questions surrounding their interpretation still remain unanswered, but they have been a recent topic of renewed interest in the literature (Bedard et al 2010;Katzner et al 2009;Logothetis et al 2007;Xing et al 2009). …”
mentioning
confidence: 99%